2019
DOI: 10.1017/aaq.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Communities on the Mesa Verde Cuesta

Abstract: This article systematically and quantitatively characterizes interaction dynamics and community formation based on changes in spatial patterns of contemporaneous households. We develop and apply a geospatial routine to measure changing extents of household interaction and community formation from AD 600 to 1280 on the Mesa Verde cuesta in southwestern Colorado. Results suggest that household spatial organization was shaped simultaneously by the maintenance of regular social interaction that sustained communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This analysis focused on maize because it was a primary food source for ancestral Pueblo people to meet their caloric needs (Coltrain and Janetski 2013; Varien et al, 2000). The local catchment areas for FVC, MCGHV and YJP were defined as a 2‐h walk (roundtrip) from the center of the village because prior studies have shown that a 2‐km catchment reasonably encompasses the area that a single community might use for intensive agriculture (Reese et al, 2019; Varien et al, 2000:52). Any year when less than half of the local catchment was within the maize farming niche probably resulted in an increased probability of climate‐induced food shortages.…”
Section: A Us Southwest Case Study Of Acute Climate Stressmentioning
confidence: 99%
“…This analysis focused on maize because it was a primary food source for ancestral Pueblo people to meet their caloric needs (Coltrain and Janetski 2013; Varien et al, 2000). The local catchment areas for FVC, MCGHV and YJP were defined as a 2‐h walk (roundtrip) from the center of the village because prior studies have shown that a 2‐km catchment reasonably encompasses the area that a single community might use for intensive agriculture (Reese et al, 2019; Varien et al, 2000:52). Any year when less than half of the local catchment was within the maize farming niche probably resulted in an increased probability of climate‐induced food shortages.…”
Section: A Us Southwest Case Study Of Acute Climate Stressmentioning
confidence: 99%
“…They are descriptive, graphic devices that do serve to identify semi-cyclic tendencies and possible discontinuities through time. Examples include [79], who examine the frequency of interpersonal violence against population size through time, and [80], in which the number of communities and the population size of a study area are plotted against each other, using line colors and symbol sizes to put these into the contexts of estimated maize production levels and average community sizes (Fig. 4).…”
Section: Noise Versus Chaos Versus Bifurcationsmentioning
confidence: 99%
“…It would have to encompass several different models, such as Bocinsky and Kohler's (2014) reconstruction of the annual rain-fed maize farming niche (the area where temperature and rainfall are sufficient to successfully grow maize in a specific year), a reconstruction of estimated population densities broken down by households per square kilometer in temporal increments as small as possible (Schwindt et al 2016;Ortman et al 2016), and frequency data for the types of sites that might be expected in any particular setting by temporal period (Ortman et al 2007), and so forth. Essentially, the model would be predictive of where communities (e.g., Reese et al 2019) and agricultural landscapes might be centered across the landscape at any particular time over the four-century period during which agriculture took hold.…”
Section: Creating a Heritage Management Plan: A Four-mentioning
confidence: 99%